Noise from mechanical ventilation systems in residential buildings - Abramkina Darya (E3S Web of Conferences, 2023)
Modern people spend up to 90% of their time indoors. Therefore, the research aimed to identify noise sources from engineering equipment, and developing recommendations for their elimination was an urgent scientific task. The paper considers the problem of noise pollution from mechanical ventilation systems in residential buildings. One of the most common errors in conducting acoustic calculations is the exclusion of noise generated by regulating devices, which significantly contribute to the final sound pressure levels at the outlet of the ventilation grate. The results of field studies are presented; they prove the need to normalize permissible noise levels in non-residential premises of an apartment and develop a legislative framework for measuring noise in hybrid ventilation systems. Practical recommendations for designing exhaust ventilation systems with a prefabricated vertical duct have been developed. It has been found that the replacement of throttle valves with iris diaphragms and the installation of silencers on prefabricated channels and apartment withdrawals, given the influence of the vortex zone from control devices, reduce the overall noise level from the ventilation system.